2020
DOI: 10.1101/2020.06.16.154054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population genomic time series data of a natural population suggests adaptive tracking of environmental changes

Abstract: 14While the evolutionary fitness of natural populations is affected by a multitude of environmental 15 factors, theory predicts that selective responses are in principle limited. However, we lack empirical 16 knowledge on the magnitude of different selection pressures natural populations adaptively track. 17Here, we developed a framework to investigate the quantitative and qualitative complexity of the 18 effectively acting selection regime using population genomic time series data. We applied the 19 approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

6
0

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…First, θ is known to be unbiased under neutrality and constant population growth (population growth rate constantly >1 through time) only (Subramanian 2016). These assumptions are probably not met in multivoltine taxa under a multivariate, fluctuating selection regime that undergo seasonal boom‐bust cycles (Pfenninger and Foucault 2020). Also, LD and divergence time estimates lose accuracy under nonneutral conditions (Kumar 2005; Slatkin 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, θ is known to be unbiased under neutrality and constant population growth (population growth rate constantly >1 through time) only (Subramanian 2016). These assumptions are probably not met in multivoltine taxa under a multivariate, fluctuating selection regime that undergo seasonal boom‐bust cycles (Pfenninger and Foucault 2020). Also, LD and divergence time estimates lose accuracy under nonneutral conditions (Kumar 2005; Slatkin 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, pervasive selection by adaptive tracking in conjunction with the seasonally fluctuating population size in both species with an exponential increase over several generations in summer with a setback during a single generation in winter (Pfenninger and Foucault 2020) may explain the strongly skewed TD distribution toward negative values both in isolated and nonisolated regions. Simulations have shown that demographic fluctuations alone can produce such a pattern (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every possible mutation is practically always present in the population and in larger lakes, perhaps even in every clonal lineage. This almost permanent presence of exhaustive genetic variation should offer excellent opportunities for adaptive tracking of changing environmental conditions (Pfenninger and Foucault 2020), moreover since clonal reproduction should help to avoid stochastic loss of beneficial mutations (Kimura 1962;Messer and Petrov 2013). In addition, the occasional seasonal sexual reproduction allows to recombine favourable variation together.…”
Section: Discussionmentioning
confidence: 99%
“…The only solution to overcome this limitation is measuring genomic change over the actual course of climate change, i.e., tracking populations through time. Such time-for-time approaches are currently being implemented and already allowed the tracking of adaptive trajectories and quantification of the selection regime in natural populations (Pfenninger and Foucault, 2020). The GEA space for time approach can also be embedded in the time-for-time framework by building up time-series of repeated GEA.…”
Section: Gea In Light Of Climate Changementioning
confidence: 99%